Beta Rasa: Emotion Regulation Program to Reduce Young Offenders Anxiety in LPKA Kupang - Juliana Marlin Y Benu; Rizky Pradita Manafe; Engelina Nabuasa (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2021)
. Anxiety is one of the emotional problems experienced by young offenders in LPKA (Lembaga Pembinaan Khusus Anak/Juvenile Detention Center) Kupang and this condition has a negative impact on their rehabilitation process. The condition requires psychological intervention. This research aimed to understand the impact of the Beta Rasa Program in reducing anxiety. Beta Rasa Program focuses on improving young offender’s emotional regulation ability. This research was a quasi-experiment with one group pretest-posttest design. In total, there were 20 young offenders participating in this program for 4 sessions. Paired sample t-test was used to analyze data in this research. Young offender’s anxiety was measured by Beck Anxiety Inventory (BAI). The research showed a significant decrease in young offenders’ anxiety (t = 2.116, p = 0.02) after they joined Beta Rasa Program. The effect size of this program was 0.41. The result indicates that Beta Rasa Program has a moderate effect to reduce anxiety.